A master of masters in cardiac surgery: Lawrence H. Cohn - You, Scarllet X. (Journal of Thoracic Disease, 2015)
In February, we feel great honor to have Dr. Lawrence H. Cohn (Figure 1) as the distinguished editorial board member of Journal of Thoracic Disease. Now, let’s take a look at Dr. Cohn’s journey to a master of masters in cardiac surgery.